Cover Feature: Bio‐Waste‐Derived Hard Carbon Anodes Through a Sustainable and Cost‐Effective Synthesis Process for Sodium‐Ion Batteries (ChemSusChem 1/2023). Issue 1 (19th December 2022) - Moon, Hyein; Innocenti, Alessandro; Liu, Huiting; Zhang, Huang; Weil, Marcel; Zarrabeitia, Maider; Passerini, Stefano
Abstract : The Cover Feature shows the sustainable cycle of hard carbon, the anode of choice for sodium‐ion batteries, produced from hazelnut shell bio‐waste, which is a highly abundant material in Europe. The developed hard carbon offers improved electrochemical properties, such as initial coulombic efficiency, specific capacity, long‐term stability, and rate capability in sodium‐ion batteries. More information can be found in the Research Article by H. Moon et al .